Catalysts of High School Students Entrepreneurial Intention as a Contribution to Achieving SDGs - Jihan Nibras Jauharah; Choirul Nikmah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to identify the factors that are catalysts for the formation of entrepreneurial intentions in students of SMA Negeri 1 Gedangan, with a focus on the influence of family economic education and peer groups through the mediation of economic literacy. Method: The research method used is quantitative with an explanatory approach. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), and referring to the Theory of Planned Behavior (TPB). Results: The results of the study indicate that family economic education does not have a significant direct effect on entrepreneurial intentions, but has a positive and significant effect on students' economic literacy. Meanwhile, peer groups have been shown to have a positive and significant effect on economic literacy and entrepreneurial intentions. Economic literacy also has a positive and significant effect on entrepreneurial intentions, and mediates the relationship between family economic education and peer groups with entrepreneurial intentions. Novelty: These findings emphasize the important role of economic literacy as a link between the social environment and family in forming entrepreneurial intentions among adolescents. Therefore, increasing economic literacy at the secondary education level is a strategic key in fostering the entrepreneurial spirit of the younger generation.